First-Principles Calculations and Experimental Study of H+-Irradiated Zr/Nb Nanoscale Multilayer System; Metals; Vol. 11, iss. 4 - Laptev R. S. Roman Sergeevich; Svyatkin L. A. Leonid Aleksandrovich; Krotkevich D. Dmitry; Stepanova E. N. Ekaterina Nikolaevna; Pushilina N. S. Natalia Sergeevna; Lomygin A. D. Anton Dmitrievich; Ognev S. O. Sergey Olegovich; Semek K. Kshishtof; Uglov V. V. Vladimir Vasiljevich (2021, 2021)
Title screen